A study on the relationship between parent-child coviewing of television and cognitive development of the child. - Zhao, Jinqiu. (2008)
This study was aimed to prove the positive relationship between parent-child coviewing of TV and preschoolers’ coginitive development. The participants comprised five-year-old preschoolers form a childcare centre at a university in Beijing, China. Both survey and experiment methods were employed to take in-depth information about the preschoolers’ television viewing habits.